Polyester composite material based on slag modification and application of polyester composite material in well lid and pipeline

By using slag-modified polyester composite materials in manhole covers and pipeline materials, combining medium alkali glass fibers, chopped basalt fibers and modified slag, the problems of poor toughness and low strength of existing materials are solved, and high mechanics are achieved Material preparation of performance and hydrophobic properties meets the needs of modern infrastructure construction.

CN119461952AInactive Publication Date: 2025-02-18CHINA PLASTICS NEW MATERIAL TECH (JILIN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410643128.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing manhole covers and pipeline materials have problems such as poor toughness, low strength, wear resistance, easy corrosion and complex manufacturing processes, which are difficult to meet the needs of modern infrastructure construction.

Method used

Using slag-modified polyester composite material, melting through a twin screw extruder by adding medium alkali glass fiber, chopped basalt fiber and modified slag, and using unsaturated polyester as binder and antioxidant. Blend extrusion to prepare composite materials with high mechanical properties and hydrophobic properties.

Benefits of technology

It significantly improves the mechanical strength, wear resistance and hydrophobic properties of the material, reduces the occurrence of agglomeration, realizes effective utilization of slag, reduces costs, and the performance of the material meets the application requirements of manhole covers and pipelines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004853918000000031
    Figure BDA0004853918000000031
Patent Text Reader

Abstract

The invention discloses a polyester composite material based on slag modification and application of the polyester composite material in well lids and pipelines, and belongs to the technical field of composite materials. The raw materials comprise, by weight, 25-35 parts of unsaturated polyester, 10-15 parts of medium-alkali glass fiber, 15-20 parts of chopped basalt fiber, 125-175 parts of modified slag, 2-4 parts of an antioxidant, 0.1-0.3 part of germanium dioxide, and 1-3 parts of a lubricant. The medium-alkali glass fibers and the basalt fibers are added into the prepared composite material, so that the mechanical strength of the material is improved; polyester is used as a binder, so that the stability is improved, and the mechanical property of the material is further improved; the slag is modified, so that the performance of the material is remarkably enhanced, the effective utilization of the slag is realized, and the cost is saved. Therefore, the prepared composite material has stable and efficient mechanical properties, wear resistance and a certain degree of hydrophobic property, effective utilization of the slag is realized, and the cost is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular, relates to a slag-modified polyester composite material and its application in manhole covers and pipelines. Background Art

[0002] Polyester is a general term for polymers obtained by polycondensation of polyols and polyacids. It mainly refers to polyethylene terephthalate (PET), and also includes linear thermoplastic resins such as polybutylene terephthalate (PBT) and polyarylate. Polyester materials have many excellent properties, such as high toughness and strength, and are a type of engineering plastics with excellent performance. Due to its excellent performance, it is also widely used in packaging, electronics, medical and health, construction, automobiles and other fields.

[0003] In recent years, as my country's infrastructure construction has entered a new cycle, the market demand for manhole covers and pipes in urban planning and road construction is huge. Most traditional manhole covers are made of cast iron, cement steel, and reinforced concrete. Cast iron has the advantages of strong bearing capacity, good temperature adaptability, simple molding and long service life, but cast iron manhole covers have the disadvantages of being not resistant to impact, prone to corrosion, loud noise when vehicles are driving, and high recycling value and easy to cause loss. Cement steel manhole covers also have strong bearing capacity, but after long-term use, the cement will fall off, the bearing capacity will decrease, and it is easy to cause accidents; reinforced concrete manhole covers have poor seismic resistance, difficult manufacturing process, easy to break, and the manhole cover is too heavy to open by one person.

[0004] Therefore, non-metallic manhole covers made of glass staple fibers and unsaturated polyester resins as the main raw materials have a simple manufacturing process, low technical content, low product cost, and no recycling value, and are receiving more and more attention. However, this type of composite material has poor toughness and low strength, and it is difficult to meet the requirements of today's manhole covers and pipes. Therefore, it is urgent to invent a polyester composite material that can solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a slag-modified polyester composite material and its application in manhole covers and pipelines.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A slag-modified polyester composite material is prepared by the following steps:

[0008] The unsaturated polyester was placed in an oven at 80°C and dried for 12 hours. The dried unsaturated polyester, medium-alkali glass fiber, chopped basalt fiber, modified slag, antioxidant, GeO2 (germanium dioxide, catalyst) and lubricant were added into a twin-screw extruder and melt-blended and extruded to obtain a slag-modified polyester composite material.

[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 25-35 parts of unsaturated polyester, 10-15 parts of medium-alkali glass fiber, 15-20 parts of chopped basalt fiber, 125-175 parts of modified slag, 2-4 parts of antioxidant, 0.1-0.3 parts of germanium dioxide, and 1-3 parts of lubricant.

[0010] Furthermore, the unsaturated polyester is 191 unsaturated polyester.

[0011] Furthermore, the antioxidant is one of antioxidant 1010 and antioxidant 264.

[0012] Furthermore, the lubricant is one of pentaerythritol stearate and paraffin.

[0013] The addition of medium-alkali glass fiber not only improves the strength of the composite material, but also improves the acid resistance of the composite material; basalt fiber is an excellent reinforcement material that can greatly improve the mechanical properties of the composite material and has good compatibility with polyester; unsaturated polyester as a binder can, on the one hand, bond the medium-alkali glass fiber and basalt fiber with the filler modified slag to form a whole; on the other hand, it can fix the relative position of the medium-alkali glass fiber and basalt fiber in the composite material, and give play to the synergistic effect of unsaturated polyester, medium-alkali glass fiber and basalt fiber. In addition, unsaturated polyester can also protect the fiber from mechanical damage, transfer stress, and withstand part of the external force; antioxidants can not only prevent the oxidation of raw materials during processing, but also improve the antioxidant properties of composite materials.

[0014] Furthermore, the modified slag is prepared by the following steps:

[0015] S1. In a three-necked flask equipped with a stirring device, ethylenediamine, undecanoic acid, dicyclohexylcarbodiimide (DCC, a dehydrating agent) and toluene were mixed and stirred evenly, and reacted for 2 hours in a water bath at 45°C. After the reaction was completed, the mixture was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 1; the ratio of ethylenediamine, undecanoic acid, dicyclohexylcarbodiimide and toluene was 6.4 g:18.6 g:20.6 g:75 mL;

[0016] The amino group on ethylenediamine and the carboxyl group on undecanoic acid undergo an amidation reaction. Under the action of a dehydrating agent, the reaction can be carried out under relatively mild conditions. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of ethylenediamine, only one amino group on ethylenediamine participates in the reaction to obtain intermediate 1. The specific reaction process is shown below:

[0017]

[0018] S2, drying the slag in an oven at 100 ° C, adding it to a vertical ball mill to grind it into powder, mixing it with N, N-dimethylformamide (DMF), adding it to a magnetic stirring device, putting in a magnet, starting stirring, dispersing for 30 minutes, so that the slag powder is evenly dispersed in N, N-dimethylformamide, evacuating the device, passing N2 gas, adding γ-glycidyloxypropyltrimethoxysilane (silane coupling agent KH-560), setting the reaction temperature to 60 ° C, reacting for 4 hours, the reaction is completed, filtering, washing with ethanol, and then drying in a vacuum drying oven for 2 hours to obtain pre-modified slag; the ratio of slag, N, N-dimethylformamide, and γ-glycidyloxypropyltrimethoxysilane is 5.0g:100mL:7.5g;

[0019] The chemical composition of slag includes oxides such as CaO, SiO2, Al2O3, MgO, MnO, and Fe2O3, among which SiO2 has the highest content. These oxides contain a lot of -OH on their surfaces, which can introduce epoxy groups by reacting with KH-560 to obtain pre-modified slag.

[0020] S3, add N, N-dimethylformamide and pre-modified slag to a flask, disperse evenly by ultrasonication for 30 minutes, add intermediate 1, slowly heat to 80°C, and start magnetic stirring (speed 1000r / min), stop heating after stirring for 6 hours, let it stand, filter after the temperature in the bottle drops to 30°C, wash with anhydrous ethanol 3-4 times, and freeze-dry to obtain modified slag; the ratio of N, N-dimethylformamide, pre-modified slag, and intermediate 1 is 100mL:10g:15g;

[0021] The epoxy group on the pre-modified slag reacts with the amino group on the intermediate 1, causing the epoxy group to open to generate a hydroxyl group, thereby obtaining the modified slag;

[0022] The slag is ground into powder and then modified. The surface of the modified slag is grafted with organic molecular chains, that is, an organic layer is formed on its surface, which can greatly improve the interfacial compatibility between the modified slag and polyester, thereby promoting the uniform dispersion of the modified slag in the polyester and reducing the occurrence of agglomeration. The modified slag is not only used as a filler, but also has a high SiO2 content in the slag, which can greatly improve the wear resistance and mechanical strength of the composite material; in addition, the grafted organic molecular chain contains a long carbon chain, which belongs to a methylene chain segment and has strong hydrophobicity, which can improve the waterproof performance and toughness of the composite material, and can be interspersed in the molecular chain of polyester to improve stability; finally, the modified slag contains hydroxyl groups, which can react with the carboxyl group at one end of the polyester molecular chain, further enhancing the interaction with the polyester and improving the stability of the modified slag performance.

[0023] Another object of the present invention is to provide an application of the composite material in a manhole cover and a pipe; and to provide a method for preparing the manhole cover and the pipe:

[0024] The polyester composite material, tert-butyl peroxide and zinc stearate are mixed and heated to dissolve, poured into a corresponding mold, and subjected to hot molding and curing molding, and after cooling, demolded to obtain a manhole cover or a pipe;

[0025] Among them, tert-butyl peroxide plays a role of thermal curing, and zinc stearate plays a role of demoulding.

[0026] Beneficial effects of the present invention:

[0027] 1. The composite material prepared by the present invention greatly improves the mechanical strength of the material by adding medium-alkali glass fiber and basalt fiber, and the unsaturated polyester can bond it well, improve the stability, and further improve the mechanical properties of the material;

[0028] 2. Using slag as filler and modifying the slag significantly enhances the material's wear resistance, mechanical properties and a certain degree of hydrophobicity, reduces the occurrence of agglomeration, and achieves effective utilization of slag, saving costs.

[0029] Therefore, the polyester composite material prepared by the present invention has stable and efficient mechanical properties and a certain degree of hydrophobicity, and realizes the effective utilization of slag, thereby saving costs. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] Preparation of modified slag:

[0033] S1. In a three-necked flask equipped with a stirring device, 6.4 g of ethylenediamine, 18.6 g of undecanoic acid, 20.6 g of DCC and 75 mL of toluene were mixed and stirred evenly, and reacted for 2 h in a water bath at 45° C. After the reaction was completed, the mixture was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 1;

[0034] S2, 5.0g of slag was dried in an oven at 100°C, added to a vertical ball mill and ground into powder, mixed with 100mL DMF, added to a magnetic stirring device, put in a magnet, started stirring, dispersed for 30min, so that the slag powder was evenly dispersed in N,N-dimethylformamide, the device was evacuated, N2 gas was introduced, 7.5g of silane coupling agent KH-560 was added, the reaction temperature was set to 60°C, the reaction was carried out for 4h, the reaction was completed, filtered, washed with ethanol, and then dried in a vacuum drying oven for 2h to obtain pre-modified slag;

[0035] S3. Add 100 mL of N,N-dimethylformamide and 10 g of pre-modified slag into a flask, disperse evenly by ultrasonication for 30 min, add 15 g of intermediate 1, slowly heat up to 80 °C, and start magnetic stirring (speed 1000 r / min). After stirring for 6 h, stop heating and let it stand. After the temperature in the bottle drops to 30 °C, filter it and wash it with anhydrous ethanol three times. Freeze-dry it to obtain modified slag.

[0036] Example 2

[0037] Preparation of modified slag:

[0038] S1. In a three-necked flask equipped with a stirring device, 12.8 g of ethylenediamine, 37.2 g of undecanoic acid, 41.2 g of DCC and 150 mL of toluene were mixed and stirred evenly, and reacted for 2 h in a water bath at 45° C. After the reaction was completed, the mixture was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 1;

[0039] S2, drying 10.0g of slag in an oven at 100°C, adding it to a vertical ball mill and grinding it into powder, mixing it with 200mL DMF, adding it to a magnetic stirring device, putting in a magnet, starting stirring, dispersing it for 30min, so that the slag powder is evenly dispersed in N,N-dimethylformamide, evacuating the device, passing N2 gas, adding 15g of silane coupling agent KH-560, setting the reaction temperature to 60°C, reacting for 4h, and completing the reaction, filtering it with suction, washing it with ethanol, and then drying it in a vacuum drying oven for 2h to obtain pre-modified slag;

[0040] S3. Add 200 mL of N,N-dimethylformamide and 20 g of pre-modified slag into a flask, disperse evenly by ultrasonication for 30 min, add 30 g of intermediate 1, slowly heat up to 80 °C, and start magnetic stirring (speed 1000 r / min). After stirring for 6 h, stop heating and let it stand. After the temperature in the bottle drops to 30 °C, filter it, wash it with anhydrous ethanol 4 times, and freeze-dry it to obtain modified slag.

[0041] Example 3

[0042] 25 g of 191 unsaturated polyester was placed in an oven at 80°C and dried for 12 h. The dried unsaturated polyester, 10 g of medium-alkali glass fiber, 15 g of chopped basalt fiber, 125 g of modified slag prepared in Example 1, 2 g of antioxidant 1010, 0.1 g of GeO2 and 1 g of pentaerythritol stearate were added to a twin-screw extruder and melt-blended and extruded to obtain a slag-modified polyester composite material.

[0043] Example 4

[0044] 30 g of 191 unsaturated polyester was placed in an oven at 80°C and dried for 12 h. The dried unsaturated polyester, 12.5 g of medium-alkali glass fiber, 17.5 g of chopped basalt fiber, 150 g of modified slag prepared in Example 2, 3 g of antioxidant 264, 0.2 g of GeO2 and 2 g of paraffin were added to a twin-screw extruder and melt-blended and extruded to obtain a slag-modified polyester composite material.

[0045] Example 5

[0046] 35 g of 191 unsaturated polyester was placed in an oven at 80°C and dried for 12 h. The dried unsaturated polyester, 15 g of medium-alkali glass fiber, 20 g of chopped basalt fiber, 175 g of modified slag prepared in Example 2, 4 g of antioxidant 264, 0.3 g of GeO2 and 3 g of paraffin were added to a twin-screw extruder and melt-blended and extruded to obtain a slag-modified polyester composite material.

[0047] Comparative Example

[0048] Ordinary slag of equal mass was used to replace the modified slag in Example 5, and the remaining steps were the same as those in Example 5.

[0049] The following performance tests were performed on Examples 3-5 and Comparative Examples:

[0050] The national standard GB / T 23858-2009 "Manhole Cover" is used to measure the tensile strength, bending strength and compression strength of the sample;

[0051] The national standard GB / T 14216 is used to measure the hydrophobicity;

[0052] The measured results are shown in the following table:

[0053] Test items Example 3 Example 4 Example 5 Comparative Example Tensile strength / mpa 92 98 103 77 Bending strength / mpa 213 227 240 181 Compression strength / mpa 114 126 137 85 Wetting tension / mN / m 32.2 34.7 36.1 25.5

[0054] It can be seen from the above table that the mechanical properties and hydrophobic properties of the composite material prepared in this embodiment are higher than those of the control example, and effective utilization of slag is achieved. The tensile strength, bending strength and compressive strength are higher than the national standards, and it has important application value in the field of manhole covers and pipelines.

[0055] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0056] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A polyester composite material based on slag modification, characterized in that: Prepared by the following steps: The unsaturated polyester was placed in an oven at 80° C. and dried for 12 hours. The dried unsaturated polyester, medium-alkali glass fiber, chopped basalt fiber, modified slag, antioxidant, germanium dioxide and lubricant were added into a twin-screw extruder and melt-blended and extruded to obtain a slag-modified polyester composite material.

2. The slag-modified polyester composite material according to claim 1, characterized in that: The modified slag is prepared by the following steps: S1, ethylenediamine, undecanoic acid, dicyclohexylcarbodiimide and toluene were mixed and stirred evenly, and reacted for 2 hours in a water bath at 45°C. After the reaction was completed, the mixture was filtered and distilled under reduced pressure to obtain intermediate 1; S2, drying the slag in an oven, adding it to a vertical ball mill to grind it into powder, mixing it with N,N-dimethylformamide, adding it to a magnetic stirring device, stirring it, dispersing it for 30 minutes, introducing N2 gas after evacuation, adding γ-glycidyloxypropyltrimethoxysilane, reacting it at 60°C for 4 hours, and after the reaction is completed, filtering it, washing it, and vacuum drying it for 2 hours to obtain pre-modified slag; S3. Add N,N-dimethylformamide and pre-modified slag into a flask, disperse by ultrasonic for 30 minutes, add intermediate 1, heat to 80°C and start magnetic stirring, stir for 6 hours and then stop heating, let stand until the temperature in the bottle drops to 30°C, filter, wash, and freeze-dry to obtain modified slag.

3. The slag-modified polyester composite material according to claim 2, characterized in that: In step S1, the ratio of ethylenediamine, undecanoic acid, dicyclohexylcarbodiimide and toluene is 6.4 g:18.6 g:20.6 g:75 mL.

4. The slag-modified polyester composite material according to claim 2, characterized in that: In step S2, the ratio of slag, N,N-dimethylformamide and γ-glycidyloxypropyltrimethoxysilane is 5.0 g:100 mL:7.5 g.

5. The slag-modified polyester composite material according to claim 2, characterized in that: In step S3, the ratio of N,N-dimethylformamide, pre-modified slag and intermediate 1 is 100 mL: 10 g: 15 g.

6. The slag-modified polyester composite material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 25-35 parts of unsaturated polyester, 10-15 parts of medium-alkali glass fiber, 15-20 parts of chopped basalt fiber, 125-175 parts of modified slag, 2-4 parts of antioxidant, 0.1-0.3 parts of germanium dioxide, and 1-3 parts of lubricant.

7. The slag-modified polyester composite material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010 and antioxidant 264.

8. The slag-modified polyester composite material according to claim 1, characterized in that: The lubricant is one of pentaerythritol stearate and paraffin.

9. Use of the polyester composite material according to any one of claims 1 to 8 in the field of manhole covers and pipelines.